(x^2 - 1) = (x+1)(x+1)
so
answer is <span>(x + 1)(6x – 1)</span>
Answer:
$90
Step-by-step explanation:
The total of all the items is $270. You are lucky that this is a multiple. Solve it like you were dividing 27 by 9, just add a 0. Good luck! - Justin <3
Answer:
56
Step-by-step explanation:
z varies jointly with x and y:
z = kxy
When x = 2 and y = 2, z = 7.
7 = k(2)(2)
k = 7/4
z = 7/4 xy
When x = 4 and y = 8:
z = 7/4 (4)(8)
z = 56
Answer:
get a piece of graphing paper and count out the squares and then when you make the triangles you should have your answer.
Step-by-step explanation:
all i know is that it's not the third one hope this helps!
Answer:
24/30
Step-by-step explanation: